The Level and Composition of Public Sector Debt in Emerging Market Crises - Rother, Bjoern (IMF Working Papers; Working Paper ;, 2006)
The paper examines the evolution of public sector debt levels and structures in 12 emerging market countries around the time of financial crises. In particular, it focuses on whether the debt situation of sovereign borrowers became more vulnerable in the aftermath of crises. The principal findings are that (i) debt levels tend to increase significantly post-crisis, and (ii) countries often experience more rigid debt structures following such events, with an increase in the share of external public debt to multilateral creditors and a greater exposure of the domestic banking system to sovereign debt.